Low Reynolds aerodynamics and propeller-wing interaction for the Mars airplane - Daniele, Sirigatti (2017)
This dissertation is representative of the study the author carried on during his internship in the Department of Space Transportation at the Japan Aerospace Exploration Agency (JAXA) in Sagamihara, Japan. The Mars Airplane is a UA V (Unmanned Air Vehicle) that is currently under development at JAXA, within the framework of the MELOSI (Mars Exploration with a Lander-Orbiter Synergy) 2020/2030 program. A JAXA in-house CFD (Computational Fluid Dynamics) Structured code was used to investigate the behavior of a NACAOO 12 airfoil for the Mars Airplane at low Reynolds numbers (4xl04 ), in order to compare the results with existing experimental data. A structured C-Type mesh generator was prograInmed in Fortran90 to build a grid topology suitable for the study. First tests were run on a 2D mesh to assess the suitability of the mesh topology to the CFD solver. Then, a series of 3D LES (Large Eddy Simulation) computations were run at different angles of attack and grid resolutions as mesh sensitivity study, to find the best compromise between solution accuracy and computational time. Subsequently, an Actuator Blade Model for the propeller was investigated and partially implemented. Finally, the CFD results were compared with wind tunnel tests performed in the Low speed wind tunnel at the Institute of Fluid Science at Tohoku University, Japan. The 3D LES results showed good accordance with the experimental data without propeller, however due to time constrains, it was not possible to develop a working Actuator Blade Model to properly simulate the propeller-wing interaction. Nevertheless, a literature review of past and present actuator blade models are thoroughly discussed in the present study as basis for future developments.